Exploring the relationship between nursing students' knowledge and attitudes towards climate change and their psychological distress: a cross-national investigation - Ali D. Abousoliman; Ateya Megahed Ibrahim; Hasan Abualruz; Hussein M. Magdi; Donia Elsaid Fathi Zaghamir; Ahmed Alhowimel; Ahmed Hashem El-Monshed; Heba E. El-Gazar; Mohamed A. Zoromba (BMC, 2024)
Abstract Background Climate change poses a worldwide challenge with anticipated exacerbation in the future, resulting in irreversible consequences. Nursing students may be vulnerable to experiencing psychological effects associated with climate change. Aim The current study aimed to investigate the relationship between nursing students' knowledge and attitudes toward climate change and their psychological distress. Method This descriptive cross-sectional study recruited 377 nursing students from three universities located in Saudi Arabia, Jordan, and Egypt in the Middle East. Data collection was conducted using scales for assessing nursing students' knowledge and attitudes towards climate change and their psychological distress. Correlations were assessed and multiple regression analysis was conducted to explore the predictors of students' psychological distress. Results The current study showed that knowledge regarding climate change significantly and positively correlated to the attitude toward climate change (r = 0.213), then again, the score of psychological distress significantly and negatively correlated to the score of students' knowledge and attitude regarding climate change (r = − 0.182 and − 0.110 respectively). Regression analyses showed that academic achievement had the strongest positive impact on students' psychological distress, while knowledge regarding climate change and attitude toward climate change had negative impacts (β = 0.381, β=-0.205, and β=-0.045 respectively). Moreover, knowledge and attitude regarding climate change were found to be significant predictors of students' psychological distress, collectively accounting for 18.2% of the observed variance. Conclusions/Implication for future practice The findings highlight the importance of incorporating climate change into nursing education programs. By enhancing nursing students' knowledge and attitudes towards climate change, there is potential to reduce their psychological distress. This study underscores the need for curriculum reforms that integrate climate change topics, aiming to foster a well-informed and resilient future nursing workforce.